2021
DOI: 10.1007/s00394-020-02463-2
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of fructose intake in adolescence for fatty liver indices in young adulthood

Abstract: Purpose To examine the association between fructose intake in adolescence and fatty liver indices (hepatic steatosis index (HSI), fatty liver index (FLI)) in young adulthood. Methods Overall, 246 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had a fasting blood sample in adulthood (18–36 years), at least two 3-day weighed dietary records for calculating fructose intakes and other fructose-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
6
0
3
Order By: Relevance
“…Previous results of the DONALD study indicated that the intake of flavonoids from fruits and vegetables was inversely associated with fatty liver indices (59) and that large amounts of high glycaemic carbohydrates in the evening might increase fatty liver values (60) . Furthermore, no association was found between fructose intake and fatty liver indices in adulthood (61) . The age of the considered study populations at fatty liver indices measurement during adulthood was very young (around 21 years) indicating that lifestyle in young age can have an influence on early development of liver steatosis.…”
Section: Discussionmentioning
confidence: 84%
“…Previous results of the DONALD study indicated that the intake of flavonoids from fruits and vegetables was inversely associated with fatty liver indices (59) and that large amounts of high glycaemic carbohydrates in the evening might increase fatty liver values (60) . Furthermore, no association was found between fructose intake and fatty liver indices in adulthood (61) . The age of the considered study populations at fatty liver indices measurement during adulthood was very young (around 21 years) indicating that lifestyle in young age can have an influence on early development of liver steatosis.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Lambert et al [ 29 ] have shown that, compared to the control subjects, de novo lipogenesis is 3% higher in the NAFLD subjects. Although contradictory findings exist, most of the epidemiological and clinical studies have shown the association between high fructose consumption (majorly in the form of HFCS) and the risk of NAFLD causation and other metabolic complications, including obesity, insulin resistance, and metabolic syndrome[ 30 - 34 ].…”
Section: Dietary Changes and Nafldmentioning
confidence: 99%
“…HFCS (ГФУ) содержит фруктозу и глюкозу в разных пропорциях в зависимости от целевого пищевого продукта: концентрация фруктозы может достигать 90%, но доминируют 42 или 55%. В некоторых странах (США и Япония) HFCS (ГФУ) -важный ее источник [4,13,23]. Фруктоза как компонент сахарозы и HFCS (ГФУ) в качестве подсластителя играет важную роль в индустрии пищевых продуктов.…”
unclassified
“…Роль фруктозы в развитии НАЖБП в отдельных популяционных группах. Хотя НАЖБП чаще отмечается у лиц старшего возраста, с развитием эпидемии ожирения отмечается быстрый рост НАЖБП в юной популяции [7,23,32]. Эксперты свидетельствуют, что НАЖБП -наиболее частая причина болезней печени у детей и подростков в США и, возможно, в остальных индустриальных странах [32].…”
unclassified
See 1 more Smart Citation